Uganda : Technical Assistance Report-Report on Government Finance Statistics. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Assistance Report discusses technical advice and recommendations given by the IMF mission to the authorities of Uganda regarding compilation and dissemination of government finance statistics and public sector debt statistics according to international standards. Automation of the collection of source data for extra-budgetary units and local governments is recommended, first through the use of data collection templates and second through incorporation of these institutional units into the Integrated Financial Management and Information System. Historical data on the stock of arrears and related repayments should also be provided to enable assessment of progress on reducing and clearing arrears.